Poly[2]catenanes-based hydrogels prepared by hydroxyl-yne click chemistry - Jinsa Li; Ziqing Hu; Hanwei Zhang; Xiaofan Ji (Supramolecular Materials)
Polycatenanes as a typical type of mechanically interlocked polymers (MIP), composing of some interlocked cycles through topology bonding has been extensively investigated. However, the comprehension regarding polycatenanes-based materials still lags behind other kinds of MIP. Therein, polyrotaxanes and slide-ring gels were able to fabricate in water to produce hydrogel. Hydrogel materials play an important role in tissue engineering, cell culture, flexible devices and other fields because of their softness and good biocompatibility. However, there was rare reports concerning polycatenanes-based hydrogels. Here, we prepared poly[2]catenanes-based hydrogel G12 incorporating hydrogen bonds through hydroxyl‑yne click reactions from M1 and M2. Comparative tests of substituting M2 with M3 involving mechanical bonds only, hydrophobic alkyl diols M4 and hydrophilic ethylene glycol M5 demonstrated that the mechanical bonds and hydrogen bonds could significantly enhance the hydrogel properties. Besides, temperature and acid responsiveness of G12 was elucidated.